Efficacy and tolerability of brivaracetam in the treatment of epilepsy: literature review and own experience - O. A. Pylaeva; K. Yu. Mukhin (Русский журнал детской неврологии)
Background. Despite significant advances in epileptology, approximately 30 % of patients suffer from drug-resistant epilepsy. Numerous approaches are currently available to treat epilepsy; however, there are still many patients with treatment-resistant disease, in whom surgery is impossible and alternative methods (vagus nerve stimulation and ketogenic diet) are ineffective. Thus, searching for new effective antiepileptic drugs (AED) for these patients remains highly relevant. In this article, we reviewed available publications and provided own results on the efficacy and tolerability of brivaracetam (Briviact®) in patients with intractable focal epilepsy.Materials and methods. The study included 8 patients aged between 16 and 35 years (mean age 18.3 years; 2 males and 6 females) with intractable focal epilepsy treated at the Svt. Luka’s Institute of Child Neurology and Epilepsy between February 1st, 2017 and September 1st, 2018.All patients received brivaracetam as an additional AED for the treatment of focal and bilateral convulsive seizures. Patients were followed up for 1 to 7.5 months. Brivaracetam was added to 1 or 2 AED (valproate, topiramate, or carbamazepine/oxcarbazepine) at a dose of 100–200 mg/day divided into 2 doses.Results and discussion. Good therapeutic effect (more than 50 % reduction in seizure frequency) was registered in 4 patients (50 %). Two patients (25 %) achieved a 25–50 % reduction in seizure frequency. Minimal clinical efficacy with no effect was observed in one patient (12.5 %). One patient (12.5 %) had aggravation of focal and motor seizures. Brivaracetam significantly reduced the severity (intensity and duration) of epileptic seizures in 70 % of patients. Four patients demonstrated substantial improvements on electroencephalogram (decreased epileptiform activity). One patient had complete suppression of epileptiform activity. Brivaracetam was most effective for bilateral convulsive seizures: 4 out of 5 patients experienced complete relief of these seizures.Brivaracetam demonstrated good tolerability: no side effects were registered in this study. Six out of 8 participants (75 %) currently continue treatment with brivaracetam. It is important that none of the patients had to stop brivaracetam due to poor tolerability. Of note, all of study participants started to receive brivaracetam because they had seizures resistant to multiple (more than 2–3) AED.Conclusion. Our findings suggest high efficacy and good tolerability of brivaracetam in patients with focal epilepsy. Our results are also consistent with the data reported by foreign authors.